2021
DOI: 10.1021/acsami.1c04164
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization of Temozolomide-Resistant Pediatric Diffuse Midline Glioma Using Potent Nanoencapsulated Forms of a N(3)-Propargyl Analogue

Abstract: The lack of clinical response to the alkylating agent temozolomide (TMZ) in pediatric diffuse midline/intrinsic pontine glioma (DIPG) has been associated with O 6 -methylguanine-DNA-methyltransferase (MGMT) expression and mismatch repair deficiency. Hence, a potent N(3)propargyl analogue (N3P) was derived, which not only evades MGMT but also remains effective in mismatch repair deficient cells. Due to the poor pharmacokinetic profile of N3P (t 1/2 < 1 h) and to bypass the blood−brain barrier, we proposed conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Moreover, the risk signature was closely related to genomic alterations, which reinforces the notion that abnormally activated target genes do not act alone but crosstalk with other important factors affecting survival outcomes, including the TERTp mutation, MGMTp methylation, and chr 7+/10- status. Previous studies have reported a link between these genomic alterations and survival outcomes, but the present results facilitate further investigation of the mechanisms underlying tumor progression ( Brat et al, 2018 ; Galbraith et al, 2020 ; Heravi Shargh et al, 2021 ). Furthermore, we found that radiotherapy failed to promote survival outcomes in grade II patients, likely increasing only their financial and social burden.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, the risk signature was closely related to genomic alterations, which reinforces the notion that abnormally activated target genes do not act alone but crosstalk with other important factors affecting survival outcomes, including the TERTp mutation, MGMTp methylation, and chr 7+/10- status. Previous studies have reported a link between these genomic alterations and survival outcomes, but the present results facilitate further investigation of the mechanisms underlying tumor progression ( Brat et al, 2018 ; Galbraith et al, 2020 ; Heravi Shargh et al, 2021 ). Furthermore, we found that radiotherapy failed to promote survival outcomes in grade II patients, likely increasing only their financial and social burden.…”
Section: Discussionsupporting
confidence: 54%
“…Shargh et al developed three nanodelivery systems of TMZ analogue (N3Propargyl) including an apoferritin (AFt) nanocage, a sulfobutyl ether β-cyclodextrin (SBE-β-CD) nanocomplex, and SBE-β-CD in nanoliposomes and tested on 2D-spheroids and 3D obtained from DIPG cell lines resistant to TMZ. The formulations were efficacious in reducing the tumor sphere size [ 79 ].…”
Section: Nanoparticles and Brain Cscs Compartmentmentioning
confidence: 99%
“…13,14,[236][237][238][239][240][241][242] Recently, the development of nanotechnologies allows to reformulate TMZ to enhance therapeutic efficiency with the evasion of MGMT enzyme. 243 In addition, pulsed ultrasound and convection-enhanced delivery (CED) have been applied…”
Section: Combination With Immunotherapy and Chemotherapymentioning
confidence: 99%
“…However, the clinical of outcomes are not satisfied due to the unmethylation of the O 6 ‐methylguanine‐DNA methyltransferase (MGMT) associated facilitation of DNA damage repair, and relatively intact blood–brain barrier (BBB) 13,14,236–242 . Recently, the development of nanotechnologies allows to reformulate TMZ to enhance therapeutic efficiency with the evasion of MGMT enzyme 243 . In addition, pulsed ultrasound and convection‐enhanced delivery (CED) have been applied to temporally disrupt the BBB and increase the concentration of drug delivery in tumor area, as a result, to enhance the sensitivity of chemotherapies and radiotherapy 244,245 …”
Section: Radio‐resistance and Current Radio‐sensitization Strategiesmentioning
confidence: 99%